Between persistence and change in Latin America: Did the recent expansion of higher education reduce educational inequality by social origins? - Mella San Martin, C (2021)
The aim of this thesis is to explore the effect that the recent expansion of higher education has had on the role of inequality by social origins in attendance to this level in Latin America. To do so, the following 12 countries were included in the analyses: Bolivia, Brazil, Chile, Colombia, Costa Rica, Dominican Republic, Ecuador, Mexico, Panama, Paraguay, Peru, and Uruguay. Particular attention is paid on Chile, an adjudicative case within the region as this piece gradually reveals.